THE IMPLEMENTATION OF PROVISION CORPORATE SOCIAL RESPONSIBILITY (CSR) TO COMMUNITY SOCIAL LIFE BY PT. BANK TABUNGAN NEGARA OF DENPASAR BRANCH OFFICE - Anak Agung Sagung Ngurah Indradewi (DUTA BANGSA UNIVERSITY INDONESIA, 2020)
Basically, by implementing CSR there are many benefits that will be received. One of them is if the company finds other potential in the area where the company is developing its production, the community and the government will support more quickly the existence of the company, because the image that the company has built has been good with the implementation of CSR programs and the most important is the impact felt by the community from the program The company's CSR is very positive. Based on the background above, the main problem is 1) How is the implementation of provision Corporate Social Responsibility (CSR) to the community social life by PT Bank Tabungan Negara of Denpasar Branch Office. 2) What factors are inhibitors of the implementation of Corporate Social Responsibility (CSR) by PT. Bank Tabungan Negara of Denpasar Branch Office?. The methodology used in the preparation of this scientific work is 1) The type of research is to use the type of empirical research (law in action); 2) The nature of the research is descriptive; 3) Data and data sources, namely primary data as main data and secondary data in the form of legal material is used as support data; 4) Data collection techniques are carried out with the technique of collecting document studies, interviews (interviews), observations / observations in the context of research the application of the provision of Corporate Social Responsibility (CSR) to the community social life by PT. Bank Tabungan Negara in Denpasar Branch Office; and 5) Data processing and analysis, after the legal data that has been collected is processed and analysed qualitatively and quantitatively, the analysis results are presented in descriptive analysis. Based on the description above, it can be concluded that the application of the provision of Corporate Social Responsibility (CSR) to the community social life by PT. Bank Tabungan Negara in Denpasar Branch Office is mandatory to carry out, in accordance with the mandate of Article 74 of Law No.40 of 2007 concerning Limited Liability Companies and Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies. PT. Bank Tabungan Negara is a limited liability company that the business is engaged in banking. There are 2 (two) methods for treating CSR in PT. Bank Tabungan Negara in Denpasar branch office, namely: the first method of Cause Branding, is the Top Down approach. The company determines what social and environmental issues must be addressed, and the second method of Venture Philanthropy, is the Bottom Up approach. The company helps various non-profit parties in the community in accordance with the needs and desires of the community. Inhibiting Factors of PT. Bank Tabungan Negara in applying Corporate Social Responsibility (CSR), which can be seen from 2 factors, namely Internal inhibiting factors and external inhibiting factors